STEM salaries in Russia: the importance of human capital and institutional factors - A. E. Putintseva (Цифровая социология)
In the age of digital transformation, there is an increasing discussion about human resource shortages. In particular, IT professionals, and specialists in science and technology (STEM – Science, Technology, Engineering and Mathematics) in general. One of the decisive factors in attracting and retaining a highly skilled workforce is the level of compensation, so it is important to understand what determinants affect its level in Russia, which is the focus of this study. The influence of human capital (special experience and availability of higher education) and institutional factors (organization size, economic sector, organization profile) were considered. The data of the National Research University Higher School of Economics Russian Monitoring of Economic Situation and Health for 2010–2020 were used for the analysis. The paper presents a detailed description of the final sample (N = 4 674). The J. Mintzer wage equation is used as the main econometric model. The results show that the level of financial compensation increases when a STEM specialist has higher education, works in a large and commercial organization. Work experience has no effect on compensation. The profile of the organization (technical or not) also did not show an unambiguous result in this study.